2009
DOI: 10.1530/rep-09-0235
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen metabolism by the equine embryo proper during the fourth week of pregnancy

Abstract: Estrogen production by the trophoblast is considered important in early equine pregnancy and leads to high concentrations in yolk-sac (Y-S) fluid. The embryo proper is a potential site for their action. We examined estrogen metabolism in the embryo proper because some actions of estrogens are derived from locally formed metabolites. The embryo proper, as well as separated extraembryonic tissues, of conceptuses collected about day 25 of pregnancy, were incubated with 3[H]-estrone (E 1 ) and 3 [H]-estradiol (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…Despite the fact that estradiol has also been suggested as the most probable signaling candidate responsible for maternal recognition of pregnancy and intrauterine migration for the llama blastocyst (32), our results do not show an effect of embryo signaling on uterine blood flow. Larger quantities of estradiol secreted by the equine blastocyst compared to the llama embryo (32,33), could explain the described effect in mare uterine blood flow and the absence of it in llamas.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Despite the fact that estradiol has also been suggested as the most probable signaling candidate responsible for maternal recognition of pregnancy and intrauterine migration for the llama blastocyst (32), our results do not show an effect of embryo signaling on uterine blood flow. Larger quantities of estradiol secreted by the equine blastocyst compared to the llama embryo (32,33), could explain the described effect in mare uterine blood flow and the absence of it in llamas.…”
Section: Discussionmentioning
confidence: 93%
“…The vast differences in uterine and endometrial vascular irrigation during the early phase of embryo development, between species that display different embryonic strategies to signal its presence to the dam, could be related to the secretion of vascular stimulants into the uterine lumen by the embryo (17). In this regard, several studies have demonstrated that the Day 16 bovine embryo (29), and specially the equine embryo, as early as Day 12 (30,33) produce and secrete estrogen, a molecule involved in inducing uterine contractility (26) and significant increases in uterine blood flow (31). Thus, during preimplantation embryo development, in the bovine this molecule would be secreted into just one uterine horn, while in the mare it would be evenly distributed between both horns and the uterine body, inducing the previously described vascular changes.…”
Section: Discussionmentioning
confidence: 99%
“…Yolk sac endoderm and trophoblast cells also express amino acid transporters such as SLC2A1 (Gibson et al 2018), a glucose transporter acting to nourish the earliest stages of embryonic development. By day 14-16, yolk sac is hormonally active, expressing a high level of P450 aromatase (CYP19A1; (Walters et al 2000)), ESR2 (Rambags et al 2008) and 17B-HSD (Raeside et al 2009) as well as PGF2A and PGE (Stout & Allen 2002) and the oxytocin receptor (Budik et al 2012) indicating the yolk sac trophoblast actively regulates oestrogen and prostaglandin metabolism and bioactivity.…”
Section: Yolk Sacmentioning
confidence: 99%
“…By Days 18-20 of pregnancy, estrone is the main estrogen present in yolk sac fl uid (Raeside et al 2009 ). Local metabolism of estrogens plays a role in mediating the actions of estrogen and also contributes to regulating bioavailability as estrone is much weaker estrogen than estradiol (Zhu and Conney 1998 ).…”
Section: Estrogen Synthesis By the Equine Conceptusmentioning
confidence: 99%
“…Estrone-to-estradiol conversion only occurs to a small extent in the wall of the bilaminar yolk sac. Both the embryo proper and extraembryonic tissues conjugate estrone and estradiol with sulfoconjugation dominating over glucuronidation (Raeside et al 2009 ). The endometrium also contributes to conjugation of estrone and estradiol, with levels of conjugation being higher than trophoblast tissue (Raeside et al 2004 ).…”
Section: Estrogen Synthesis By the Equine Conceptusmentioning
confidence: 99%